Penerapan Model Pembelajaran Role Playing pada Materi Debat untuk Meningkatkan Keaktifan dan Prestasi Belajar Siswa Kelas X MIPA 3 MAN 2 Bantul - Sumardiasih Sumardiasih (Nusantara: Jurnal Pendidikan Indonesia, 2021)
This study aims to improve the activeness and achievement of learning in Indonesian language debate materials by using role-playing learning models in grade X students of MIPA 3 MAN  2 Bantul even semester of the 2019/2020 academic year. This research was conducted from January to April 2020. This study's subject was a Grade X student of MIPA 3 MAN 2 Bantul, who numbered 25 students. The indicators examined in this study are the activeness and learning achievement of students. The research design uses a class action research model. The study consisted of 2 cycles, each of which consisted of 3 meetings. The data collection method uses observation method, questionnaires, and written tests. The study results can be concluded that applying the Role-Playing learning model can increase the activeness and achievement of learning in the field of study of Bahasa Indonesia debate material in students grade X MIPA 3 MAN  2 Bantul even semester 2019/2020. Student activity in the first cycle of 61.50% increased in the second cycle to 88.50%. In the first cycle, student learning achievement based on an average score of 65.55% increased in the second cycle to 82.28%. Similarly, the number of students completed in the first cycle by 36% rose to 80%. The successful use of Role-Playing learning models can be used as an alternative learning model to improve students' activeness and learning achievement.